Detection of Genetic Diversity of Sambar Deer (Cervus unicolor) Using Inter Simple Sequence Repeat Molecular Markers - Alfiya, Sofyana; Putra, Widya Pintaka Bayu; Fanani, Anhar Faisal; Wibowo, Ari; Suhardi, Suhardi (Universitas Bengkulu, 2025)
The Sambar deer (Cervus unicolor) is a species facing the threat of population decline due to poaching. This study aims to analyze the genetic diversity of Sambar Deer from East Kalimantan using the Inter Simple Sequence Repeat (ISSR) molecular marker with primers P01 and P02. There were 10 sambar deer, eight females and two males, from Pembibitan Ternak dan Hijuan Pakan Ternak, Penajam Paser Utara, East Kalimantan. Blood samples were obtained from the jugular vein using an EDTA project tube. The samples were processed through Polymerase Chain Reaction (PCR) and electrophoresis to detect polymorphism patterns. This research showed a DNA average purity of 1.382 and an average concentration of 13.205; primer P01 produced three haplotype diversity, and primer P02 produced two haplotype diversity. The Polymorphic Information Content (PIC) values were 0.632 for primer P01 and 0.304 for primer P02. Dendrogram analysis revealed three population clusters based on genetic diversity. The conclusion indicates polymorphism, with primer P01 showing higher polymorphism than primer P02.